Towards Smart Transportation: The Impact Of Transportation Policies On Mobility In The Outskirts (Case Study: Mijen Suburban Area In Semarang City) - Purwantoro, Agus Budi; Ariani, Firga; Hutama, Adhiyaksa Satria (International Journal Labs, 2024)
This study evaluates the success of transportation policies in addressing increased travel frequency, expanded travel distribution, and changes in transportation mode choices to achieve sustainable suburban transportation. The research was conducted through a mobility analysis survey in Mijen District, Semarang City, Indonesia. Data collection focused on two main areas: first, travel frequency was analyzed using a trip generation model (Y), factoring in variables such as car ownership (X1), motorcycle ownership (X2), travel efficiency (X3), safety (X4), comfort (X5), and environmental friendliness (X6) of public transport. Second, travel distribution and mode choice were analyzed to understand community preferences for travel destinations and modes of transport. The findings revealed that land use changes in Mijen resulted in a 32% improvement in road quality and increased mobility. Recent transportation policies, such as the introduction of Bus Rapid Transit (BRT) and online transportation services, significantly influenced mobility. Mobility grew by 23.8% per year, with changes in the travel frequency model: Y = 1.957 before BRT (2012-2014), Y' = 1.927 after BRT (2014-2016), and Y'' = 1.860 after online transportation (2016-present). Transportation service demand and capacity were balanced, with load factors of 69.7% before BRT, 54.1% after BRT, and 72% after online transportation. The share of public transport users increased from 36% before BRT to 60% after online transportation services. This research contributes to developing smart city and transportation concepts by providing insights into the impact of transportation policy changes in suburban areas.